Answer:
8x + (6x + 6) = 90°
x = 6°
Step-by-step explanation:
because it is a right angle, the sum of the angles = 90°
8x + (6x + 6°) = 90°
simplify:
14x + 6° = 90°
subtract 6° from each side:
14x = 84°
divide both sides by 14:
x = 6°
Answer:
The standard form of the quadratic equation is x² + 3·x - 4 = 0
Step-by-step explanation:
The standard form of a quadratic equation is a·x² + b·x + c = 0
Given that the expression of the quadratic equation is (x + 4)·(x - 1) = y, we can write the given expression in standard form by expanding, and equating the result to zero as follows;
(x + 4)·(x - 1) = x² - x + 4·x - 4 = x² + 3·x - 4 = 0
The standard form of the quadratic equation is x² + 3·x - 4 = 0
The graph of the equation created with MS Excel is attached